2002
DOI: 10.1007/s10350-004-6390-y
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Trial of the Effect of Metronidazole on Pain After Closed Hemorrhoidectomy

Abstract: Closed hemorrhoidectomy results in high patient satisfaction and low pain scores. The use of postoperative metronidazole did not reduce postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 22 publications
0
41
0
6
Order By: Relevance
“…It is believed that the analgesic effect of metronidazole is due to improved wound healing. However, there are other studies such that of Balfour et al [21], which have shown that metronidazole does not reduce post-operative pain.…”
Section: Discussionmentioning
confidence: 93%
“…It is believed that the analgesic effect of metronidazole is due to improved wound healing. However, there are other studies such that of Balfour et al [21], which have shown that metronidazole does not reduce post-operative pain.…”
Section: Discussionmentioning
confidence: 93%
“…O papel do espasmo esfincteriano e colonização bacteriana como contribuinte desta não foi totalmente elucidado 9,10 . Diversos procedimentos e técnicas cirúrgicas, como a hemorroidopexia com uso de grampeador circular tem demonstrado redução desta e um retorno mais rápido para atividades cotidianas 3,6 . No entanto, seu alto custo limita seu uso rotineiro.…”
Section: Discussionunclassified
“…Seu uso oral apresenta resultados conflitantes, com benefício Keywords: pain, postoperative; metronidazole; hemorrhoids; hemorrhoidectomy. duvidoso 6,7,9 . Em 1998, Carapeti et al 7 demonstraram, em estudo prospectivo e randomizado, que o metronidazol oral significativamente diminuiu a dor pós operatória nos dias 5, 6 e 7 após hemorroidectomia aberta por diatermia, além de determinar melhor satisfação do paciente e retorno precoce ao trabalho.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This has been indicated in a recent randomized controlled trial [6] based on the ''opinion'' that post-hemorrhoidectomy pain is due to sphincter spasm; furthermore, he suggests the use of metronidazole supposing that postoperative pain is due to infection at the site of anal wounds. The utility of this antibiotic-based approach was suggested in 1998 [6] but has not be confirmed in a recent randomized controlled trial [7], although topical application of metronidazole ointment seems to reduce postoperative pain [8].…”
mentioning
confidence: 99%